SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KANDIDAT PENERIMA BEASISWA BBM (STUDI KASUS STMIK SINAR NUSANTARA) - Utami, Yustina Retno Wahyu (JURNAL GAUNG INFORMATIKA, 2010)
The scholarship provided for the students who are taking either D3 or bachelor degree (S1) in STMIK SinarNusantara is alocated from Dirjen DIKTI which in here is represented by Regional VI of Kopertis throughSTMIK Sinar Nusantara. So far, the selection process of the scholarship receiver candidates is still carried outmanually so that it is possible enough to have unwanted mistakes appeared either in the data recording process or the determination of the scholarship receiver candidates. To overcome the mentioned problem, it is necessary to develop a decision support system in determining the candidates  of the scholarship receiver. This decision support system has 9 criterion and uses mathematic model. The system which is developed uses the help of data flow diagram and entity relationship diagram. the result of this prototype will be able to help the selection team in scoring the candidates whether they are less proper, proper, or very proper to get the scholarship. The score ranking will be able to help the selection team in determining the scholarship receiver.